Structural Geology of Rocks and Regions - Davis G. H. George (Hoboken, John Wiley & Sons, Inc., 2012)
When author George Davis conceptualized the cover for the first edition of STRUCTURAL GEOLOGY OF ROCKS AND REGIONS, he wanted to emphasize that learning comes from doing, and that new insight springs from careful, detailed examination of field relationships, viewed at all scales from individual rocks to entire regions.He asked illustrator David Fischer to combine details from four particular photos into a single painting that would be the cover illustration of that first edition. The challenging structural relationships of folded rocks envelope the geologist, and the curvature of th back and neck;torqued as eyes and brain move ever closer to the clipboard, show the classic body language of geologic mapping.